THE RHYTHM OF GLOBALIZATION AND PERSISTENCE OF THE SOCIO-CULTURAL SIGNIFICANCE OF GOLD JEWELLERY IN ASANTE, GHANA - Isaac Kwabena Agyei; Peggy Fening; Charles Adu-Boachie (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
Gold jewellery is one essential art form by which the people of Asante express their sociocultural identity and distinctiveness. It is perceived however that this heritage is being eroded in recent times through the rhythm of globalization. This study provides empirical evidence on the persistence or otherwise of the sociocultural significance of gold jewellery in Asante. The study employed the explanatory design approach. Data was obtained from a total of 198 respondents comprising traditional rulers, goldsmiths and the general public through the use of questionnaire designed in open and close ended patterns and personal observations. The statistical package for the social sciences (SPSS) computer package was used for data analysis, whilst descriptive statistical tools such as frequency and percentage were used to analyze the facts sought from the questionnaire. The study observed that a lot of myths that surrounded gold jewellery have been demystified as a result of education, religion, trade liberalization, ICT and the current political dispensation which gives people the right of choice and makes it difficult to control production, designing and sale of products. While this trend of change is of great significance to national building, on the other hand it offsets the preservation objective of the Asante culture, by which the Asante historical culture may lose its value.